2012
DOI: 10.1111/j.1399-0012.2012.01653.x
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of humoral immunity after intravenous immunoglobulin replacement therapy in heart recipients with post‐transplant antibody deficiency and severe infections

Abstract: IgG hypogammaglobulinemia is a risk factor for infection in heart recipients. We assessed reconstitution of humoral immunity after non-specific intravenous immunoglobulin (IVIg) replacement therapy administered to treat secondary IgG hypogammaglobulinemia in heart recipients with severe infections. The study population comprised 55 heart recipients who were administered IVIg (IVIg group) and 55 heart recipients with no severe infectious complications (control group). An event was defined as a severe infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 11 publications
1
41
0
Order By: Relevance
“…Two studies published by Carbone et al . found no impact of IVIg administration on rejection rate . However, the studies published by Yamani demonstrated a significant reduction in the occurrence of grade 2 and 3 rejection , and these results were supported by the results from Nathan et al .…”
Section: Summary Of Key Characteristics Of Studies Investigating Treamentioning
confidence: 55%
“…Two studies published by Carbone et al . found no impact of IVIg administration on rejection rate . However, the studies published by Yamani demonstrated a significant reduction in the occurrence of grade 2 and 3 rejection , and these results were supported by the results from Nathan et al .…”
Section: Summary Of Key Characteristics Of Studies Investigating Treamentioning
confidence: 55%
“…After IVIG therapy, humoral immune status in these patients was comparable with 55 non-hypogammaglobulinemic controls. Furthermore, the mean number of infections in the 6 months after IVIG therapy was significantly lower than that before IVIG therapy [82]. A double-blinded randomized controlled crossover trial in which 11 lung transplant recipients with hypogammaglobulinemia (defined as IgG <5 g/l) received IVIG and placebo for 3 months each did not find a reduced risk of bacterial infections under IVIG [83].…”
Section: Antibody Replacement Therapy In Ihgmentioning
confidence: 97%
“…Almost all available reports describe the use of IVIG therapy, and data on the use of SCIG for IHG are virtually absent. Adverse effects of antibody replacement therapy are not discussed in most reports, but in three reports on post-solid organ transplantation hypogammaglobulinemic patients (combined n = 79, of whom 67 received ‡3 IVIG infusions), no moderate or severe adverse reactions were reported [81][82][83]. Discontinuation of antibody replacement therapy due to adverse effects is not mentioned in any of the reports.…”
Section: Antibody Replacement Therapy In Ihgmentioning
confidence: 99%
“…Pooled analysis of four studies revealed a reduced mortality in the IVIG (n = 167) group when compared to the control (n = 288) group(Figure 2; OR 0.34, 95% CI 0.17-0.69, I 2 = 0%, and Chi 2 = 2.20). Both studies did not find significant difference in mean number of rejection episodes between the IVIG treatment and control groups (0.86 vs 0.65, respectively; P = 0.33, 21 and 0.32 ± 0.60 vs 0.26 ± 0.57, respectively; P = 0.69) 23. Two of the six studies reported graft rejection outcome, but the reported data could not be pooled for meta-analysis 21,23.…”
mentioning
confidence: 95%
“…Two of the six studies reported graft rejection outcome, but the reported data could not be pooled for meta-analysis 21,23. 21,23-25 Unlike the other studies, Carbone et al 33 2018 used IVIG as a secondaryprophylaxis; nevertheless, a reduced mortality was also observed in the IVIG group (P = 0.006).…”
mentioning
confidence: 99%